Chasing Arizona : one man's yearlong obsession with the Grand Canyon state - Lamberton, Ken, 1958- (The University of Arizona Press, 2015)
"The book is a personal account of the author's year spent 'chasing Arizona' by going to as many places as possible in fifty-two weeks to learn about Arizona's history, symbols, food, people, and quirky customs. It is part travelogue, part history book, part essay collection and covers the whole state from border towns to the Four Corners"--Provided by publisher